Migration in Bulgaria : Current Challenges and Opportunities - Garrote Sanchez, Daniel (World Bank, Washington, DC, 2022)
This paper presents evidence on trends, profiles, drivers, and impacts of Bulgarian emigration. The analysis shows that emigration is mostly led by sizable wage differentials and that emigrants tend to be young, contributing to a decrease in the working-age population in the country, particularly in rural regions. Emigration is not associated with unemployment reductions, evidencing rigidities in the labor market, but leads to wage gains for workers with similar skills. Furthermore, migration has not led to national skill shortages of doctors, and the rate of return migration is high, especially for Bulgarians who migrated to other EU countries. Some challenges emerge when returnees try to reintegrate into the Bulgarian labor market, calling for potential policy interventions to address these issues.